Impact of additive manufacturing on supply chain elements: a literature review-based study. (28th February 2022) - Shuaib, Mohd; Haleem, Abid; Javaid, Mohd
Additive manufacturing (AM) technologies are advancing and narrowing down their limitations in fields and have dramatically changed the way product is designed, prototyped, manufactured and become part of the supply chain (SC), thus providing customers with wider options. This paper tries to address the impact of AM on different elements of the SC and pursues an inductive research approach. The methodology adopted considers both positive and negative views for comparative studies of AM with traditional one. The proposed research explores the implication of the adoption of AM technologies on the supply chain. The topics range from simple SC issues to legal concerns, marketing strategy about new manufacturing technology, and even in non-business areas to explore the technical attributes. The adoption of AM in the industry is low and there is less academic research available. The study shows that AM affects the conventional manufacturing systems and needs to be upgraded in every stage of the SC, from raw material supply to the final delivery system.